Study protocol for a cluster randomised controlled trial to assess the effectiveness of user-driven intervention to prevent aggressive events in psychiatric services - Välimäki, Maritta; Yang, Min; Normand, Sharon-Lise; Lorig, Kate R.; Anttila, Minna; Lantta, Tella; Pekurinen, Virve; Adams, Clive E. (BioMed Central, 2017)
Background